Pengaruh Pemahaman Peraturan Perpajakan Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Pada Pelaku Umkm Di Kota Bekasi - Wirya, Wirya; Zahran, Wahidin Septa (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The decline in the compliance ratio of MSME actors in Bekasi City, due to the lack of understanding of applicable tax regulations and tax sanctions, is evidenced by the instability of the level of taxpayer compliance ratio for MSME actors in Bekasi City every year. This study aims to analyze the understanding of tax regulations, and tax sanctions on taxpayer compliance with MSME actors in Bekasi City. This research involved 61 MSME actors. The data collection method is carried out by surveying using a guestionsnaire method cosisting of guestions related to understanding tax regulations, and tax sanctions. The data obtained were analyzed using descriptive statistical technigues and multiple linear regression analysis. The results of the study show that taxpayer’ understanding of tax regulations has an effect of 42,9%, tax sanctions have an effect of 29,7% on taxpayers’ compliacnce with MSME actors in Bekasi City.This finding emphasizes the importance of increasing understanding of tax regulations and tax sanctions on the level of tax payer compliance with MSME actors in Bekasi City. The Directorate General Of Taxes needs to provide awards for MSME taxpayers who are always tax-compliant as a form of DGT’s appreciation to taxpayer who are always consistent in paying and reporting taxes on time. So that MSME actors who receive the award can increase the consistency of taxpayer compliance with MSME actors in Bekasi City.